Aerodynamic detailed design of an Unmanned Aerial Vehicle with VTOL capabilities - Coelho, Vasco (2022)
ALF/ENGAER 139424-L Vasco Luís Martins Ferreira Coelho. Examination Committee: Chairperson: BGEN/EngEl 119923-E Rui Fernando da Costa Ferreira; Supervisor: MAJ/EngAer 131603-G Joao Vítor Aguiar Vieira Caetano, Dr. Frederico José Prata Rente Reis Afonso; Member of the Committee: Prof. Dr. Afzal Suleman